Interdisciplinary Surgical Management of Simultaneous Bone Metastases in Uterine Cervix Carcinoma: Total Replacement of Temporomandibular Joint and Stabilization of the Cervical Spine. (2nd September 2020) - Eckardt, André M.; Reichstein, Klaus; Heine, M.
Metastasis to the mandibular condyle and cervical spine in oncologic patients is rare, and clinicians should therefore be alert if patients present with such suspicious lesions for further clinical and pathological examinations.  A 58-year old female patient with uterine cervical cancer initially presented with mild left condylar dysfunction. CT-imaging revealed a progressive osteolytic lesion of the left condyle and at the same time CT-scans revealed an osteolytic lesion of the cervical spine. Further metastatic bone lesions were ruled out. An incisional biopsy of the left condyle revealed metachronous metastasis from the uterine cervical carcinoma. Based on clinical and radiological examinations the patient underwent surgery with total alloplastic replacement of the temporomandibular joint (TMJ) and in a second surgical approach stabilization of the cervical spine. Suspicious symptoms with TMJ dysfunction in conjunction with osteolytic lesions of the maxillofacial skeleton in oncologic patients should be addressed quickly to prevent further diagnostic delay. Surgical resection of metastatic lesions should be considered as a palliative treatment option in selected patients.